2020
DOI: 10.29303/abdiinsani.v7i2.292
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Tehnologi Inseminasi Buatan Menggunakan Sperma Sexing Pada Ternak Sapi Di Kecamatan Lingsar Kabupaten Lombok Barat

Abstract: Peningkatan mutu reproduksi pada kegiatan perternakan sapi perlu terus menerus digalakkan. Hal tersebut agar terciptanya efisiensi pada usaha produksi ternak sehingga menghasilkan keuntungan finansial yang lebih baik. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk meningkatkan mutu genetik pada ternak sapi melalui inseminasi buatan menggunakan tekhnologi sperma sexing. Kegiatan ini dilakukan melalui penyuluhan, ceramah dan diskusi. Peserta yang menjadi target pelaksanaan kegiatan adalah peternak sap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
0
0
Order By: Relevance
“…The non-return rate is the percentage of animals that do not return to mate or return to estrus after the first insemination (Yuliani et al, 2020). Lombok Regency shows almost the same results, not much different from the results of the study of (San et al, 2015) showed that the NRR result of 28-35 days in Patean District was 83.44% and in Plantungan District 86.66%.…”
Section: Evaluation Based On Non-return Rate (Nrr)mentioning
confidence: 58%
“…The non-return rate is the percentage of animals that do not return to mate or return to estrus after the first insemination (Yuliani et al, 2020). Lombok Regency shows almost the same results, not much different from the results of the study of (San et al, 2015) showed that the NRR result of 28-35 days in Patean District was 83.44% and in Plantungan District 86.66%.…”
Section: Evaluation Based On Non-return Rate (Nrr)mentioning
confidence: 58%
“…Therefore, when a low viscosity was observed, it was assumed that the semen had a low concentration of spermatozoa (Sumadiasa et al, 2018). The pH of the collected semen was neutral, with a value of 7.00, which was within the normal range of 6-7 (LukmanHy et al, 2020;Dhumal et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Kacang goat is suitable for meat and leather production because it is prolific, resistant to various conditions, and well-adapted to different rearing environments, with the main product being meat (Nafiu et al, 2020). To increase their productivity, appropriate reproductive technology, such as artificial insemination (AI) can be used (LukmanHy et al, 2020). This technique aims to minimize the potential danger of disease transmission through natural mating; moreover, the used semen is selected from superior males.…”
Section: Introductionmentioning
confidence: 99%